NF-κB regulates neuronal ankyrin-G via a negative feedback loop - König, Hans-Georg (Sci Rep, 2017)
The axon initial segment (AIS) is a neuronal compartment defined by ankyrin-G expression. We here demonstrate that the IKK-complex co-localizes and interacts with the cytoskeletal anchor protein ankyrin-G in immunoprecipitation and proximity-ligation experiments in cortical neurons. Overexpression of the 270 kDa variant of ankyrin-G suppressed, while gene-silencing of ankyrin-G expression increased nuclear factor-κB (NF-κB) activity in primary neurons, suggesting that ankyrin-G sequesters the transcription factor in the AIS. We also found that p65 bound to the ank3 (ankyrin-G) promoter sequence in chromatin immunoprecipitation analyses thereby increasing ank3 expression and ankyrin-G levels at the AIS. Gene-silencing of p65 or ankyrin-G overexpression suppressed ank3 reporter activity. Collectively these data demonstrate that p65/NF-κB controls ankyrin-G levels via a negative feedback loop, thereby linking NF-κB signaling with neuronal polarity and axonal plasticity.